Mites of the family Pachylaelapidae in Bayburt Province, Turkey (Acari: Mesostigmata), with a new record and three new species - Şahi̇n, Gülhan; Özbek, Hasan Hüseyi̇n (Zootaxa, 2018)
This paper reports on mites of the family Pachylaelapidae collected in Bayburt Province, Turkey, during 2013–2015. Nine species were recorded in the genera Pachyseius, Olopachys, Pachylaelaps, and Onchodellus. Pachylaelaps (Longipachylaelaps) bayburtensis sp. nov., Onchodellus turcicus sp. nov. and O. montanus sp. nov. are described to new, and Pachylaelaps (Longipachylaelaps) vicarus is a new record for the Turkish mite fauna. New records extend the geographic range of Pachyseius masani, Olopachys hallidayi, and O. elongatus in Turkey.